2010
DOI: 10.1177/1474651409355454
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from biosimilar epoetins and insulins

Abstract: Patients with diabetes and renal failure may already be receiving biosimilar epoetin and may receive biosimilar insulin in the near future. Because these biosimilar pharmaceuticals (or follow-on biologics) are complex protein molecules manufactured in lengthy and inherently variable processes involving living organisms, they have the potential to induce an immunogenic, rather than a therapeutic, response. This response is dependent as much on the method of manufacture and formulation, as on the protein itself.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
0
22
0
2
Order By: Relevance
“…Immunogenicity can arise from minor changes in manufacturing and may emerge early or only after long-term exposure [33,34], underscoring the need for effective pharmacovigilance. for SB309 was pre-defined but not met and a post-hoc correction factor in the maintenance study was required to bring the parameters within the range [29].…”
Section: Immunogenicity Riskmentioning
confidence: 99%
“…Immunogenicity can arise from minor changes in manufacturing and may emerge early or only after long-term exposure [33,34], underscoring the need for effective pharmacovigilance. for SB309 was pre-defined but not met and a post-hoc correction factor in the maintenance study was required to bring the parameters within the range [29].…”
Section: Immunogenicity Riskmentioning
confidence: 99%
“…Some of the concerns have been legitimate, with a number of biosimilar insulins failing to meet stringent registration standards. [4] However, ongoing vigilance and extensive clinical trials will continue to be required to ensure the safety and efficacy of new biosimilar insulins.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case for recombinant human erythropoietin (epoetin alpha), for which an increased frequency of pure red cell aplasia (PRCA)-a rare, potentially fatal condition caused by the formation of anti-epoetin antibodies neutralizing both the exogenous product and endogenous erythropoietin-was observed when the reference product manufactured by Amgen (Thousand Oaks, CA) under the brand name of Epogen was licensed to Ortho Biotech (Bridgewater, NJ), under the trade name of Eprex. Retrospective analyses concluded that the differential rates of PRCA (which was associated with Eprex administration in more than 90 % of cases) was attributed to minor changes in the buffer formulation and the use of different prefilled syringes resulting in an increased immunogenicity of the therapeutic protein [18,19].…”
Section: Safety Challenges With Biosimilars Issues In Manufacturing Pmentioning
confidence: 99%